The Success of The Teaching Methods of Prophet Muhammad (PBUH) in Engineering Education - Dadach, Zin Eddine (Universitas Islam Negeri Alauddin Makassar, 2020)
Literature has shown that effective teachers have succeeded in making students feel good about school and learning, thus increasing student achievement. Moreover, students in an actively taught class do a better job of learning (memorizing) the material they are exposed to, compared to those in a passively taught section. The main goal of this paper is to show that the teaching methods of Prophet Muhammad (PBUH) are successful tools for engineering education. First, to fully deliver his message, Prophet Muhammad (PBUH) addressed the hearts of followers to become the beloved one in order to inspire them to listen to his message. Secondly, in order to maximize the effects of his message, he used a type of speech that made his followers think during his educational methods. He utilized analogies and active learning strategies to enhance the imagination and curiosity of the listeners. As utilized by The Prophet (PBUH), the literature review highlights the use of analogies and active learning have a positive impact on both performance and the motivation of students to learn. Moreover, these teaching strategies engage students in higher thinking to be deeply involved in learning. From this perspective, the success of the utilization of the teaching methodology of our Beloved Teacher (PBUH) is demonstrated by the fact that the performance of thirty-eight (69%) students was higher in a process control course than the average performance in the department. Additionally, the results also show that the combined methodology, including analogies and active learning, increased the intrinsic motivation of twenty-two (40%) students.